Measurements of air-broadening parameters of water vapour transitions in the 7520–8586 cm−1 spectral region. (1st February 2022) - Petrova, T. M.; Solodov, A. M.; Solodov, A. A.; Deichuli, V. M.; Starikov, V. I.
Abstract : The water vapour line broadening ( γ ) and shift ( δ ) coefficients for 319 lines of 11 vibrational bands 2ν3, 2ν2 +ν3, 3ν2 +ν3, 5ν2, 6ν2, ν1 +ν3, ν1 +ν2 +ν3, ν1 +2ν2, ν1 +3ν2, 2ν1, and 2ν1 +ν2 from the spectral region 7520–8586 cm –1 induced by air pressure were measured with a Bruker IFS 125 spectrometer. The measurements were performed at a spectral resolution of 0.01 cm –1 and over a wide air pressure range. The calculations of the line-shift coefficients δ were performed in the framework of a semi-classical method. The measured air-broadening coefficients γ were combined with literature data for air- and N2 -broadening coefficients γ measured for the lines in the 380–22, 593 cm –1 spectral region. Combined experimental data for N = 4110 measured coefficients γ of 76 vibrational bands of H2 O molecules were fitted to the empirical functions. The computed coefficients γ derived from the fitted parameters were statistically compared with the measurements. The vibrational dependence of the measured γ values and their compatibility is discussed. GRAPHICAL ABSTRACT: UF0001